Comparison of life regard index between veterans suffering from post traumatic stress disorder with and without history of substance abuse in Shahid Rajaee Hospital in Isfahan - M.R. Haji Abed; F. Bagheri; A.A. Asghar Nejad Farid (Afarand Scholarly Publishing Institute, 2013)
Background : Incidence of Post Traumatic Stress Disorder (PTSD) among some combatants was one of the problems of Iran-Iraq War. Several studies have shown that, this disorder have high comorbidity with other kinds of disorders such as substance abuse. Unfortunately, some imposed war veterans are involved in substance abuse, too. The current study examined the effect of some individual psychological factors on these veteranschr('39') substance abuse. The main hypothesis of this research is the existence of the significant difference between life regard index of veterans who did not history of substance abuse in comparison to veterans with a history of substance abuse. Therefore, the aim of this study is to compare this variable between two experimental groups. Materials and Methods: To achieve the research objectives, 120 veterans who were hospitalized in Shahid Rajaee Hospital in Isfahan for PTSD about 9 months were selected by available sampling method, 60 of them were with and others without substance abuse, And they were matched in terms some of demographic characteristics with each other. Then, life regard index of the subjects were evaluated by questionnaire. For data analysis, descriptive statistics (Mean, SD) and for hypothesis investigation, inferential statistics (independent T-Test) were used. Results : There was significant difference between the mean score of life regard index of those with history of substance abuse and those without it. Also, there was a significant difference between the two groups in terms of the fulfillment subscales scores. Between the two groups of subjects in terms of scores of framework subscales had no significant difference. Conclusion: positive life regard development could facilitate the prevention of substance abuse in veterans and cause immediate recovery from it.